A contribuição dos recursos organizacionais para a estratégia competitiva dos prestadores de serviços logísticos (PSLs) : estudo multicasos em empresas de transporte rodoviário de cargas de Caxias do Sul - Machado, Sandro Manoel (My University, 2016)
The strategic focus directed to the internal resources of the organizations, promoted as from the decade of the 80s, has been disseminated in various segments of the market, also calling attention to the logistics and transport sector, due to its expressive participation in the area of services and the impact of the costs with logistics, mainly the ones referring to transportation, on the invoicing of the companies. In this manner, this dissertation has the objective of verifying how the organizational resources area explored and employed in highway cargo transport companies of Caxias do Sul and how they contribute to its competitive strategy in the context of logistics. The research performed had an applied nature, a qualitative approach and an exploratory objective, of a multiple case study, by the application of in-depth interviews with the principal managers of the nine companies selected, with use of the resource matrix, and VRIO (value, rarity, imitability, and organization) for organization and analysis of data. Supported by the premises of the Resource Based View (RBV), the study enables the analysis of the inherent characteristics of the principal organizational resources of the transport companies, revealing that, although the companies have similar resources, their competitive advantages come from the heterogeneity of the manner they utilize and explore these resources.The results evidenced the predominant contribution of the intangible resources in obtaining a sustainable competitive advantage, especially of the registered trade mark and of the logistic processes, confirming the relevance of the exploration of organizational resources for the competitive strategy of the Logistics Service Providers.
O enfoque estratégico direcionado aos recursos internos das organizações, impulsionado a partir da década de 80, foi sendo disseminado em diversos segmentos do mercado, chamando a atenção também para o setor de logística e transportes, devido à sua expressiva participação na área de serviços e ao impacto dos custos logísticos, em especial o de transporte, no faturamento das empresas. Deste modo, este estudo teve por objetivo verificar de que forma os recursos organizacionais são explorados e empregados nas empresas de transporte rodoviário de cargas de Caxias do Sul e como contribuem para sua estratégia competitiva, no contexto da logística. A pesquisa efetuada teve natureza aplicada, abordagem qualitativa e objetivo exploratório, do tipo estudo multicasos, através da aplicação de entrevistas em profundidade junto aos principais gestores das nove empresas selecionadas, com uso de matriz de recursos e do modelo VRIO (valor, raridade, imitabilidade e organização) para organização e análise dos dados. Amparado nas premissas da visão baseada em recursos (Resource Based View – RBV), o estudo possibilitou a análise das características inerentes aos principais recursos organizacionais das empresas de transporte, revelando que, embora as empresas possuam recursos similares, suas vantagens competitivas provêm da heterogeneidade da forma como elas utilizam e exploram estes recursos. Os resultados evidenciaram a contribuição predominante dos recursos intangíveis na obtenção de vantagem competitiva sustentável, sobretudo da marca registrada e dos processos logísticos, confirmando a relevância da exploração dos recursos organizacionais para a estratégia competitiva dos Prestadores de Serviços Logísticos (PSLs).
Keywords: Planejamento estratégico; Planejamento empresarial; Transporte rodoviário de cargas - Caxias do Sul (RS); Logística empresarial; Strategic planning; Business planning; Trucking - Caxias do Sul (Brazil); Business logistics